Strategies of Enhancing ICT Use in the Delivery of Management Services in Public Secondary Schools in Siaya County in Kenya - Oluoch, Dornela (European Scientific Journal, ESJ, 2016)
This study was set to determine the strategies of enhancing ICT use in the delivery of services in public secondary schools in Siaya County, Kenya. Although many secondary schools introduced computers in great numbers starting early 1990s, there are limited information on their use to facilitate delivery of services in school administration and management. The extent to which ICT is being used in school management in secondary schools, the types of administrative uses of ICT by school managers and challenges affecting the integration of ICT in the management systems in secondary schools needed to be adequately addressed. This can only be achieved if there are laid down strategies of enhancing ICT use in the delivery of services in public secondary schools in Siaya County. The study was guided by Social Transformation Theory in Education and Visscher (1992) conceptual model of school information system, which were used to show the relationship between variables. The research design that used was descriptive survey. Questionnaires, Interviews and document analysis were used to collect data. The study established that schools were taking several steps to help in enhancing ICT delivery such as looking for grants from the government, prioritizing purchase of ICT equipment and using parents’ involvement to buy computers. The study recommends that effort should be made by the government to post and provide teachers skilled in ICT to each school to impart ICT skills to school managers. The study concludes that more support need to be given to schools to enable them achieve their dream of fully implementing the usage of ICT in the management of school activities.